PENGAYAAN SISTEM INFORMASI MANAJEMEN PERPUSTAKAAN INSTITUT TAZKIA DI ERA MILINEAL : STUDI KASUS PADA SLiMS - Erus Effendi (Perpustakaan Nasional RI, 2020)
Introduction. The Library of TAZKIA Islamic University college has a program in getting to the world class university library (WCU-L). To achieve the program, an information system is needed that plays an important role in helping all operational business units run effectively and efficiently, which saves time and costs. SLiMS is used by the TAZKIA library as a comprehensive information system of input data collection, membership, circulation transactions and the processing of library materials and outputs that result in easy information retrieval. This research optimizes the making of a book label (call number) collection in SliMS.Research methods. This research uses the RAD (Rapid Application Development) method consist of requirement planning, design workshop and implenentation to solve the problem of making Library Book Labels.Results and Discussion. This study produces an effective and efficient book label system that is applied optimally to SLiMS book label bibliography features and does not require any other application as a book label maker.Conclusion. This research resulted in enrichment of SLiMS bibliographic features in post-processing activities in making book labels quickly and easily as well as effectively and efficiently with low cost. The book labeling feature available in SLiMS can be utilized optimally and does not require other applications as a tool to print book labels.